Social Media, External Prestige and Students’ Attitude towards Postgraduate Enrollment: A Conditional Process Analysis across Levels of University Reputation - Gabriel Simiyu; Joyce Komen; Ronald Bonuke (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose- This paper aimed to determine the conditional effect of University reputation on the indirect process of external prestige on the relationship between social media and students’ attitude towards postgraduate enrollment. Design/Methodology- The study adopted a cross-sectional survey design, multistage random sampling in collecting data using a self-administered questionnaire. The sample size was 504 students from four universities in Kenya. Findings- Outcome indicates a partial indirect effect of social media and students’ attitude via external prestige. It further reveals a conditional effect of university reputation on the link between; social media and external prestige, and, external prestige and students' attitude. Finally, a test of the conditional indirect process is also confirmed. Practical Implications- Results of the study might help university managers and policymakers in developing effective strategies, policies, and techniques to attract potential students through social media platforms and also develop and strengthen university prestige and reputation through proper management of resources, social responsibility, and employment of qualified academic staff. Originality/value- The study findings bring new understanding concerning the indirect effect, the conditional process and highlight new insights on identifying mechanisms that exert a conditional effect on the indirect paths of the study variables.